The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fonc.2021.599018
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implementation of Proton Therapy Using Pencil-Beam Scanning Delivery Combined With Static Apertures

Abstract: Proton therapy makes use of the favorable depth-dose distribution with its characteristic Bragg peak to spare normal tissue distal of the target volume. A steep dose gradient would be desired in lateral dimensions, too. The widespread spot scanning delivery technique is based, however, on pencil-beams with in-air spot full-widths-at-half-maximum of typically 1 cm or more. This hampers the sparing of organs-at-risk if small-scale structures adjacent to the target volume are concerned. The trimming of spot scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Although PBS allows for lateral collimation of the beam through the placement of spots conforming to the target extents, it has been shown that a sharper lateral dose fall-off 15 , 16 could be achieved by a patient specific aperture. The use of aperture for PBS adds another layer of complexity for isocenter verification.…”
Section: Methodsmentioning
confidence: 99%
“…Although PBS allows for lateral collimation of the beam through the placement of spots conforming to the target extents, it has been shown that a sharper lateral dose fall-off 15 , 16 could be achieved by a patient specific aperture. The use of aperture for PBS adds another layer of complexity for isocenter verification.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that the benefit of LP from overscanning decreases with depth can be explained by the lateral scattering of protons increasing with depth. Likewise, additional lateral scattering of the proton beam in combination of collimated PBS with range shifters for shallow tumors as described in various studies 3–6,9,13,25 diminishes the effect. Future research should investigate the overscanning and spot positioning effect in potential clinical setups such as multiple energies, setups with multiple fields, in different range shifter materials and thicknesses, as well as changing the order of range shifter and aperture 3,25 …”
Section: Discussionmentioning
confidence: 97%
“…The LP is influenced by the initial spot size, multiple Coulomb scattering in matter (the patient), and optional beam shaping devices in the treatment head (‘nozzle'), such as range shifter or aperture. A sharper LP could be achieved when combining PBS with apertures or multi‐leaf collimators 3–8 . Winterhalter et al 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The pencil-beam scanning (PBS) technique with apertures can in principle be applied as well. [9][10][11] The DFO of a generated SOBP is impacted by the energy spread at the treatment nozzle exit. Here a balance between high dose rate, maximum field size, and energy spread needs to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral spreading of the proton beam is typically achieved by a single‐ or double‐scattering systems. The pencil‐beam scanning (PBS) technique with apertures can in principle be applied as well 9–11 …”
Section: Introductionmentioning
confidence: 99%